The Relationship Between Sense of Place and Nature-Based Architectural Beauty: A Comparative Case Study - Al-azzawi, Sana; İnalhan, Göksenin; Al-azzawi, Nada (Journal of Contemporary Urban Affairs, 2024)
Biophilic design, which integrates nature into the built environment, has shown positive impacts on human well-being. However, the benefits of indirect experiences of nature remain less explored, particularly in relation to the sense of place (SoP). This study investigates the relationship between nature-based architectural beauty and SoP through a comparative case study of two educational buildings with different aesthetic qualities: one classical and naturalistic, the other modernist and mechanistic. Using a quasi-experimental design, the study employs a survey-based quantitative analysis, measuring 1) SoP among users, 2) perceptions of naturalness through image-based judgments, and 3) objective measures of naturalistic beauty using image analysis. Findings indicate that users of the naturalistic building report a significantly higher sense of place, supported by perceptions of naturalness and objective measures. This suggests that environments embodying naturalistic beauty foster positive connections and place attachment. The study contributes to architectural and urban design strategies by highlighting the socio-economic benefits of nature-inspired aesthetics. By enhancing emotional and psychological well-being, such designs can lead to increased productivity, reduced stress, and stronger community ties, ultimately contributing to socio-economic development through improved quality of life and sustainable urban planning.